Dust in the Smith Cloud? A UV Investigation into the Smith Cloud’s Gas-phase Abundance Patterns - Johanna T. Vázquez; Kathleen A. Barger; Frances H. Cashman; Andrew J. Fox; Bart P. Wakker; Felix J. Lockman; Alex S. Hill; Suraj Poudel; April L. Horton; Jaq Hernández; Matthew Nuss; Alice Blake; et al. (The Astrophysical Journal)
The Smith Cloud is a high-velocity cloud (HVC) on its final approach to the Milky Way that shows evidence of interaction with the Galaxy’s disk. We investigate the metallicity and gas-phase chemical depletion patterns in this HVC using UV absorption-line observations toward two background QSOs taken with the Hubble Space Telescope/Cosmic Origin Spectrograph and H i 21 cm emission-line observations taken with Green Bank Telescope. We find evidence of silicon gas-phase depletion with [Si/S] = $-0.7{2}_{-0.26}^{+0.24}$ and [Si/O] _3 _σ  ≲ −0.05, implying the presence of dust within the Smith Cloud. Because dust is galactic in origin, this HVC could trace the return leg of a Galactic fountain or a dwarf galaxy that passed through the Galactic plane.